REVIEW KLASTER MRO DI INDONESIA DAN STRATEGI PENGEMBANGANNYA - Freddy Franciscus (Jurnal Teknologi Kedirgantaraan, 2019)
The MRO market in Indonesia is growing quite high at around 9.2% per year up to 2025, number 2 (two) after India which has an MRO market growth rate of around 10.0% per year and above China with a growth rate of around 8 .7% per year. In 2018 the Indonesian MRO market is around 1 Million US $ and only absorbed by Indonesian MRO around 30%. Most of the 70% portion of the markets that are not absorbed are the engine maintenance and component maintenance. Meanwhile, most existing MRO Indonesia is a cluster of engines and component maintenance. There is an absorption anomaly in Indonesia MRO market. The cause of the anomaly are lack of capability and capacity of Indonesia's MRO, the quality of MROs are not international standard, lack of the quantity and quality of technicians and the value chain of aircraft spare parts procurement is inefficient. The short-medium term strategies are to develop the capability and capacity of existing MROs, especially engine and component maintenance B737-800 / 900, A320-200 and ATR 42/72. Improve the quality of MRO. Improve the quality & quantity of technicians. Increasing the value chain efficiency in the procurement of aircraft spare parts. The long term strategy is to build Aerospace Park in West, Central and East Indonesia.